Climate change and crop production challenges: An overview - Chowhan, Sushan; Ghosh, Shapla Rani; Chowhan, Tushar; Hasan, Md Mahmudul; Roni, Md Shyduzzaman (Research in Agriculture Livestock and Fisheries, 2016)
Correction: 25th August 2016 - p.260 paragraph 1 line 8 'Table 2' was changed to 'Table 8' Climate change has heterogeneous effect on crop production. Potential yield of some crops were found to be decreasing in different simulation models. High temperature, drought, salinity, excessive rain fall are the major stresses faced by crops in a changing climatic condition. Coastal areas of Bangladesh are highly vulnerable to climate change. It was found that a total of 1,405.57 MT yield are lost in different crops. Data shows the production trends of many crops remaining in a steady state or their increase is very slow compared to elapse of time. Some possible adaptation measures such as sorjan system, floating bed agriculture, growing crops in raised beds, harvesting rain water, cultivation of salt and flood tolerant crop varieties etc. were suggested to reduce possible climate change risk and to cope up with the current situation. Res. Agric., Livest. Fish.3(2): 251-269, August 2016